Effects of Stationary and Transient Transport of Ozone on the Ozone Valley Over the Tibetan Plateau in Summer - Xu, Wenwen; Song, Qianqian; Li, Yajuan; Shi, Chunhua; Sun, Bo; Su, Yucheng; Tang, Zhou; Du, Yahan; Guo, Dong (Frontiers in Earth Science, 2021)
We studied the effects of the stationary and transient transport of ozone in the upper troposphere and lower stratosphere (UTLS) on the ozone valley over the Tibetan Plateau (OVTP) in summer using the daily ERA-Interim reanalysis dataset for the time period 1979–2016. We used the Lorenz circulation decomposition method to separate the stationary and transient transport of ozone into terms related to either the mean flow or eddies. The decrease in the total ozone concentration in summer is associated with the transport of ozone, which, in turn, reinforces the OVTP. The zonal (meridional) transport of ozone, which combines stationary and transient transport, strengthens (weakens) the ozone valley. The stationary zonal (meridional) transport of ozone strengthens (weakens) the ozone valley. The transient zonal (meridional) transport of ozone weakens (strengthens) the ozone valley, but this effect is weaker than that of stationary transport. The mean flow has the dominant role, especially in the stationary component. The effect of eddies on the zonal transient transport of ozone is as strong as that of the mean flow. For stationary transport, the zonal deviation of ozone transported by the zonal mean flow in the zonal (meridional) direction dominates total zonal (meridional) transport of ozone, which strengthens (weakens) the ozone valley. The transient transport of the zonal mean ozone by eddies , the zonal deviation of ozone by the zonal mean flow and the zonal deviation of ozone by eddies all have a strong effect on the ozone valley. By contrast, transient meridional ozone transport has a much weaker and the smallest effect. Both the zonal deviation of ozone by the zonal mean flow and by eddies in the meridional direction and have major roles in transient meridional transport, but their roles are the opposite of each other. The contributions of stationary and transient transport to zonal transport are consistent, whereas their contributions to meridional transport are the opposite of each other. The influence of transient transport on the formation and maintenance of OVTP is not negligible.